HUBUNGAN IMT DAN TINGKAT AKTIVITAS FISIK DENGAN KEJADIAN KOMORBID TB-DM DI KOTA SEMARANG - Mia Rahmania; Lintang Dian Saraswati; M. Arie Wuryanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Tuberculosis in an infectious disease resulted in a high number of mortality in Indonesia. Diabetes melitus recognized as an important risk factors to tuberculosis. The aim of the study was to analyze relationship BMI and physical activity level with the incidence of comorbid TB-DM in Semarang city. This study is an analytical observational study with cross sectional study design. The study population was 286 positive smear TB patients who still TB treatment from April to August 2018. The sample size in the study was 100 TB patients who selected using proportional probability with sample size and simple random sampling technique. Primary data obtained directly through interviews with respondents using questionnaires, and measurement of blood sugar to diagnose DM. Bivariate analysis using chi-square with 95% significance. The results of measurements with fasting blood sugar levels found that 29% of respondents were diagnosed with DM. The majority of respondents were 46-55 years old (27%) with mean age 44.05 years and male sex (53%). The majority of TB-DM patients have overweight IMT (72.7%) and have moderate physical activity (43.3%).Bivariate analysis showed that BMI (p=0,000) and physical activity level ((p=0,081). It can be concluded there is a relationship between BMI with the incidence of comorbid TB-DM. DM patients are expected to control increasing body weight and food intake.